(untitled) (Argos, 2025)
The analysis of the first ἀγών in Andromache (425? b. C.) to be presented below represents a sample of Euripidean rhetoric, addressed in light of its significant impact in shaping the Aristotelian rhetorical reflections. Also in line with the works of GOEBEL (1983), LLOYD (1992) and DUBISCHAR (2001), this article will attempt to show the relevance of rhetorical patterns in the interpretation of agonistic speeches and the dramatic function of ἀγών for the tragic resolution of the play.